GPX3 methylation in bone marrow predicts adverse prognosis and leukemia transformation in myelodysplastic syndrome. (28th November 2016) - Zhou, Jing‐Dong; Lin, Jiang; Zhang, Ting‐Juan; Ma, Ji‐Chun; Yang, Lei; Wen, Xiang‐Mei; Guo, Hong; Yang, Jing; Deng, Zhao‐Qun; Qian, Jun
Abstract: Epigenetic inactivation of GPX3 has been identified in various cancers including leukemia. Moreover, aberrant DNA methylation was also found as a dominant mechanism of disease progression in myelodysplastic syndrome (MDS). This study intended to explore GPX3 promoter methylation and its clinical relevance in 110 patients with MDS. GPX3 methylation was examined by real‐time quantitative methylation‐specific PCR (RQ‐MSP) and bisulfite sequencing PCR (BSP). GPX3 methylation was identified in 15% (17/110) MDS patients, and significantly higher than controls, and lower than acute myeloid leukemia (AML) patients ( P = 0.024 and 0.041). GPX3 methylated patients had older age and higher frequency of DNMT3A mutation ( P = 0.015 and 0.066). Cases with GPX3 methylation showed significantly shorter overall survival (OS) time than those with GPX3 unmethylation analyzed with Kaplan–Meier analysis ( P = 0.012). Moreover, Cox regression analysis revealed that GPX3 methylation might act as an independent prognostic indicator in MDS (HR = 1.847, P = 0.072). GPX3 methylation density was significantly increased during the progression from MDS to secondary acute myeloid leukemia (sAML) in three follow‐up paired patients. Our study concludes that GPX3 methylation in bone marrow is associated with adverse prognosis and leukemia transformation in MDS. Abstract : GPX3 methylation was identified in 15% myelodysplastic syndrome (MDS) patients, and was associated with adverse prognosis. GPX3 methylation density was significantly increased during the progression from MDS to sAML in follow‐up patients.